The Enigma of the Family Successor–Firm Performance Relationship: A Methodological Reflection and Reconciliation Attempt - Ahrens, Jan-Philipp; Calabrò, Andrea; Huybrechts, Jolien; Woywode, Michael (Entrepreneurship Theory and Practice, 2019)
Empirical studies examining firm performance following CEO succession in family firms predominantly document inferior performance of family successors. This evidence is at odds with general theoretical literature that attests a positive effect of family involvement inside the firm. To explore this enigma, we theoretically and empirically disentangle the influence of the CEO attribute family member (i.e., the CEO is affiliated to the family) on post-succession firm performance, from other, distinct CEO attributes (e.g., CEO-related human capital). Our analysis on the individual CEO level shows that after respective controls, the family member attribute is significantly positively related to post-succession firm performance.